PERAN INTELIJEN KEJAKSAAN DALAM MENGUNGKAP PERKARA TINDAK PIDANA KORUPSI - M. Dedy Iskandar Harahap; M. Yamin Lubis; Nelvitia Purba (Jurnal Ilmiah METADATA, 2021)
The rise of corrupt practices in Indonesia has made this criminal act known as an extra ordinary crime so that it also needs extraordinary law enforcement. One of the ways to enforce the law of corruption is the Attorney General's Office. The formulation of the problem in this thesis is how the intelligence duties and functions of the Prosecutor's Office according to Law Number 16 of 2004 concerning the Prosecutor's Office, what is the role of the intelligence of the Attorney in uncovering cases of corruption, what are the obstacles and efforts of the Attorney's intelligence in uncovering corruption cases. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the intelligence duties and functions of the Attorney General were as a source of information, data and support. In the investigation process, intelligence agents carry out activities in the form of target analysis, task analysis and determining operational targets to collect data and collect information that will serve as evidence that a criminal act of corruption has been detrimental to state / regional finances. In general, the role of the Attorney General's intelligence office in uncovering criminal cases of corruption has a role, namely in the case of investigations into criminal acts of corruption by the intelligence. Prosecutor's Office in order to obtain information and disclosure materials to proceed to the investigation process by a special criminal section, preventive or preventive efforts by establishing a Guard Team. and Government Security and Regional Development (TP4D) based on a letter from the Attorney General's Order, and Intelligence at the State Prosecutor's Office in the search for fugitives from the prosecution / court. The obstacles to the intelligence of the Attorney General's Office in uncovering cases of criminal acts of corruption are in the case of summoning witnesses, collecting evidence, and fear of parties being questioned regarding the intervention of related agencies. Efforts to overcome this are by extending time in the process of summoning witnesses and collecting evidence related to cases.